การพัฒนาโปรแกรมแบบขนานพร้อมแบบจำลองด้านเวลาบนหน่วยประมวลผลกราฟิก กรณีศึกษาการจำลองสึนามิ - พงษ์พัฒน์ เป้าเพ็ชร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Nowadays, high-performance personal computers can be constructed with a wide range of multicore CPUs and GPGPUs (general-purpose graphics processing units) that vary in the number and performance of processor cores. The variation makes it even more difficult to develop a parallel program that performs well on different computers and to estimate its performance on a particular computer. Also, given performance requirements for a parallel program, it is hard to determine whether a specific computer will be able to satisfy the requirements. The latter problem is the case for applications with real time constraints that guarantee to produce results within specified time. Some of these applications solve optimization algorithms that give improved results over time. Therefore, within fixed time, the speed of computation of such an application on a particular machine also determines the quality of the results. Our research focuses how to develop parallel programs on GPGPUs that solve optimization problems with real time constraints and give the best possible results. In particular, we are interested in real time tsunami simulation. The time constraints of this problem are determined by the travelling time of the first wave from the origin to the shore and the time allowed for warning and evacuation. Our parallel tsunami simulation program is based on TUNAMI program. The algorithm uses finite difference methods with nested multi-resolution regions. The original Fortran code is rewritten in C language with CUDA API. The results show that the C+CUDA version achieves good speedup and can satisfy the time constraints for real time tsunami warning for Thailand.